JCU 2017 Reviewers (Journal of Clinical Ultrasound, 2018)
Objective To evaluate the intra-and interobserver reproducibility of the cervical elastography index (EI) measurements using strain elastography (SE) with a standardized acquisition protocol. Methods In this prospective cross-sectional study, 301 women between 18 and 24 weeks of gestation underwent transvaginal ultrasound examination (TVUS). Cervical length (CL) and EI were measured using a defined region of interest (ROI) protocol positioned at the internal and external cervical os, maintaining a 5 mm standardized probe-to-cervix distance. Measurements were performed twice by Examiner 1 and once by Examiner 2. Reproducibility was assessed using the intraclass correlation coefficients (ICC) and Bland-Altman analysis. Results Intraobserver reproducibility was high for CL (ICC = 0.984) and EI (ICC = 0.991). Interobserver reproducibility was high for CL (ICC = 0.903) and high for EI (ICC = 0.910 and 0.906). Bland-Altman analysis demonstrated minimal bias and narrow limits of agreement for both measurements. Conclusion Using a standardized acquisition protocol, strain elastography-derived EI demonstrates high intraobserver and interobserver reproducibility comparable to CL measurement. These findings support its potential clinical applicability in mid-trimester cervical assessment.